2020
DOI: 10.1002/cam4.3283
|View full text |Cite
|
Sign up to set email alerts
|

From the completion of neoadjuvant chemotherapy to surgery for colorectal cancer liver metastasis: What is the optimal timing?

Abstract: Background Neoadjuvant chemotherapy (NAC) has been widely performed in the treatment of colorectal cancer liver metastasis (CRLM) patients, but the optimal timing of surgery after NAC is unclear. The aim of this study was to investigate the optimal timing of surgery. Methods From December 2010 to May 2018, 101 consecutive patients who received NAC followed by liver resection for CRLM were included in this study. The main outcome parameters were pathological response, progression‐free survival (PFS), and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Thus, a primary tumour in the right colon with a favorable pathological response is reasonable. In addition, a significant correlation between the radiological response and the pathological response was identified, consistent with a previous study (11). This Open Access Statement: This is an Open Access article distributed in accordance with the Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International License (CC BY-NC-ND 4.0), which permits the noncommercial replication and distribution of the article with the strict proviso that no changes or edits are made and the original work is properly cited (including links to both the formal publication through the relevant DOI and the license).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, a primary tumour in the right colon with a favorable pathological response is reasonable. In addition, a significant correlation between the radiological response and the pathological response was identified, consistent with a previous study (11). This Open Access Statement: This is an Open Access article distributed in accordance with the Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International License (CC BY-NC-ND 4.0), which permits the noncommercial replication and distribution of the article with the strict proviso that no changes or edits are made and the original work is properly cited (including links to both the formal publication through the relevant DOI and the license).…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence unequivocally demonstrates that NAC can significantly prolong the survival of CRLM patients who undergo liver resection (7)(8)(9). Pathological response is an important factor in the evaluation of chemotherapy efficacy and the prediction of outcomes in patients treated with NAC followed by liver resection (10,11). A favorable pathological response, which has been recognized as a predictor of improved postoperative survival, was observed in 45-57% of these patients (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer mechanism of IOPS mainly includes: Decreasing the expression of MMP-2, MMP-7, and MMP-9, increasing the expression of tissue metallopeptidase inhibitor 2 (TIMP-2), and decreasing the expression of NF-κB in cancer cells [2,3,8,9,[84][85][86][87][88][89][90][91].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Adam et al (29) found that disease progressed in about 25% of patients during the interval between NAC and surgery. Another study found that the cohort of patients who underwent resection more than 5 weeks after NAC, compared to the group that underwent less than 5 weeks after, had a worse pathological reaction and worse RFS (30). Thomas et al (13) concluded that surgery within 2 months of NAC improved long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%